PELATIHAN PEMBUATAN PILUS IKAN TUNA SIRIP KUNING (Thunnus albacares) FORTIFIKASI DAUN KELOR BAGI IBU-IBU NELAYAN DI KAMPUNG HAMADI, KOTA JAYAPURA - Indrayani, Ervina; Rumahorbo, Basa T.; Togibasa, Octolia; Ayer, Popi Ida Laila; Mandey, Vera K.; Rejauw, Korinus; Wanimbo, Efray; Tuhumena, Lolita; Paiki, Kalvin; Rumbiak, Kristhopolus K. (LPPM Uncen, 2024)
The catch from fishermen in the Hamadi village is currently sold fresh at the beach or taken to the Hamadi Fish Auction Place (TPI) for sale. The most abundant catch is yellowfin tuna (Thunnus albacares). Based on interviews with the fishermen's wives in Hamadi Village, the main issues they face are a lack of skills and technology, as well as tools and materials for processing fish products. During the fish abundance season, the fishermen's wives sell fish at lower prices due to a lack of knowledge about fish product processing and limited raw materials. The target of this activity is the fishermen's wives in Hamadi Village. The proposed solution is to conduct training on making tuna chips using moringa leaves as an additional ingredient. The community service activity took place on August 14, 2024, and was attended by 15 participants. The methods used were socialization and training (demonstration). The outcome of this community service activity was that participants gained knowledge and experience about the process of processing yellowfin tuna into fish chips (80%). Keywords: JAS Fishermen's wives; Hamadi; Chips Moringa; Tuna